Facile two-step chemoenzymatic access to natural germination inhibitor (+)-erigeronic acid A - Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2006)
A facile two-step synthesis of natural germination inhibitor 5-butyl-3-oxo-2,3-dihydrofuran-2-yl-acetic acid [(+)-erigeronic acid A, 1] has been described via highly regioselective ring opening of (R)-acetoxysuccinic anhydride with the primary enolate of butyl methyl ketone, followed by an enzymatic hydrolysis and ail in situ dehydrative cyclization pathway with 77% overall yield. Oil the basis of the present chemoenzymatic approach, (R)-configuration has been assigned to the C-2 chiral centre of the natural erigeronic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: (+)-erigeronic acid; (R)acetoxysuccinic anhydride; natural germination inhibitor; primary enolate of butyl methyl ketone; synthesis